2018
DOI: 10.1002/dmrr.3089
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and postural control deficit in adults with Type 2 diabetes

Abstract: Background Diseases induced by metabolic disorders, eg, Type 2 diabetes, has recently been linked to both sensory and motor deficit in the absence of a formal clinical diagnosis of peripheral neuropathy. Studies have demonstrated mild cognitive impairment in diabetic patients, which also plays a role in one's loss of ability to successfully perform basic motor activities. This project focused on evaluating cognitive function while maintaining balance. We hypothesized that simultaneous cognitive and motor defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Significant differences in force production error rates and signal predictability in the T2D group in motor only tasks were consistent with previous literature (Gorniak et al, 2014; Ochoa et al, 2016; Ochoa & Gorniak, 2014). Baseline cognitive function, assessed via MoCA, was reduced in the T2D group, particularly in the domain of recall/working memory, consistent with recent reports of MCI and working memory deficits in T2D (Christman et al, 2009; Creavin et al, 2011; Gorniak et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Significant differences in force production error rates and signal predictability in the T2D group in motor only tasks were consistent with previous literature (Gorniak et al, 2014; Ochoa et al, 2016; Ochoa & Gorniak, 2014). Baseline cognitive function, assessed via MoCA, was reduced in the T2D group, particularly in the domain of recall/working memory, consistent with recent reports of MCI and working memory deficits in T2D (Christman et al, 2009; Creavin et al, 2011; Gorniak et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…We do note that the 4 s windows between working memory stimuli in the N-back (cognitive) task may have contributed to the lack of group differences in the response rate findings. It is possible that additional cognitive deficits may have emerged if the time interval between cognitive stimuli was decreased or if the duration of each trial had been longer than 30 s, thereby further taxing the central nervous system (e.g., by taxing a limited channel capacity), as found in Gorniak et al (2019). All single task evaluations were performed prior to any dual tasks, which may have induced a learning effect in our study population, and thus a reduction in reaction time in the dual task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tactile sensitivity loss due to peripheral neuropathy (PN) has been implicated as the primary cause of both sensory and motor deficits in the hands and feet of PwDM [7][8][9][10]; however, our recent work has demonstrated that motor changes in PwDM occur independent of such tactile impairment, and appear to be unrelated to disease duration and severity [2][3][4][5]11]. Our data indicate other physiological factors such as vascular dysfunction and functional cortical changes as the underlying mechanism for sensorimotor changes in PwDM [2][3][4][5][11][12][13][14]. Due to the confluence of multiple systemic changes in the bodies of PwDM, the contribution of multiple systems−including sex hormone changes and impaired global hemodynamic function−to sensorimotor dysfunction prior to PN diagnosis in PwDM is fully plausible.…”
Section: Introductionmentioning
confidence: 99%